PI3K signaling in Leishmania infections - Kima, Peter E. (Cell Immunol, 2016)
PI3K signaling plays a role in the host response to Leishmania infections. At the cellular level PI3K signaling is engaged by the parasite to control several cellular processes, which ensures parasite persistence. At the systemic level, there is evidence that recruitment of regulatory cells into lesions is impaired in the absence of robust PI3K signaling. In this mini-review the more recent studies that investigated the roles of PI3K signaling in Leishmania infections are discussed.